Synthesis of Some Substituted Benzoxazole [3,4-b] imidazoles - Yaser S. Al-Jawharji (College of Education for Pure Sciences, 2008)
ABSTRACT In this paper the synthesis of 4-substituted benzoxazole [3,4-b] imidazole (9,10) and 4-aryl hexahydrobenzoxazole [3,4-b] imidazole (13,14) is reported. Glycine was treated with benzoyl chloride or p-nitrobenzoyl chloride to give N-aroyl glycine (1,2), the reaction of N-aroyl glycine with thionyl chloride followed by treatment the product (3,4) with ammonium hydroxide to give N-aroyl glycine amide (5,6). Treatment of the amide with 1-bromocyclohexanone gave N-methylene-2-hexahydrobenzoxazole) aryl amide (7,8), cyclization of this gave product (9,10), whereas the compounds (13,14) was synthesized from o-aminophenol and the acid chlorides to give N-methylene (2-benzoxazole) aryl amide (11,12) which cyclized with phosphorous oxychloride to give the products (13,14). The structure of all synthesized compounds were confirmed by physical and spectral data.